The Effect of Motivation, Discipline and Leadership on Employee Performance: The Case of Light Rail Transit (LRT) South Sumatera - Ramadani,, Lisma; Fatimah, Fatimah; Tobari, Tobari (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the effect of Work Motivation, Work Discipline, and Leadership on the Performance of South Sumatra LRT (Light Rail Transit) Employees. This type of research is Associative. The variables used by researchers are Work Motivation, Work Discipline, and Leadership. The sample in this study was 127 PKWT employees from the South Sumatra LRT (Light Rail Transit) Station, selected by Cluster Sampling. The data used in this study are primary, collected through a questionnaire method. The data analysis technique used is Multiple Linear Regression with the SPSS Program Application. The results of this study indicate that: (1) Work Motivation, Work Discipline, and Leadership together have a positive and significant effect on Employee Performance, (2) Work Motivation has a positive and significant effect on Employee Performance. (3) Work Discipline does not have a significant effect on Employee Performance. (4) Leadership does not have a significant effect on Employee Performance